Inter-sectoral Transfer of the Food for Life Settings Framework in England. (11th April 2017) - Gray, Selena; Jones, Matthew; Means, Robin; Orme, Judy; Pitt, Hannah; Salmon, Debra
Summary: Organisational settings such as schools, workplaces and hospitals are well recognised as key environments for health promotion. Whilst there is extensive literature on specific types of settings, little empirical research has investigated the transfer of frameworks between sectors. This study analyses Food for Life, an England-wide healthy and sustainable food programme that evolved in schools and is being adapted for children's centres, universities, care homes, and hospital settings. Following a case study design, we interviewed 85 stakeholders in nine settings. Food for Life's systemic framework of 'food education, skills and experience' 'food and catering quality', 'community and partnerships' and 'leadership' carried salience in all types of settings. These were perceived to act both as principles and operational priorities for driving systemic change. However, each setting type differed in terms of the mix of facilitating factors and appropriate indicators for change. Barriers in common included the level of culture-shift required, cost perceptions and organisational complexity. For settings based health promotion practice, this study points to the importance of 'frame-working' (the systematic activity of scoping and categorising the field of change) alongside the development and application of benchmarks to stimulate change. These processes are critical in the transfer of learning from between sectors in a form that balances commonality with sufficient flexibility to adapt to specific settings. Synergy between types of settings is an under-recognised, but critical, part of action to address complex issues such as those emerging from the intersection between food, health and sustainability.